Brain behavior analysis of mental stress before and after listening to Quranic recitation based on EEG signals - Silabdi, Hana; Hassan, Raini; Mahri, Nurhafizah; Md Nor, Norzaliza (IIUM Press, 2021)
Stress is a chronic problem of the modern world. According to the World Health Organization (WHO), stress is one of the most serious health problem of recent decades and is considered the main threat to individuals, occurring when they lose the balance between the difficulties of daily life and their ability to manage them. It has been shown by numerous studies that Quranic recitation is effective in calming the mind by generating Alpha activities on the human brain that indicate a state of relaxation and calmness. However, Quranic recitation and its effect on mental stress itself is still not fully investigated and understood. This research is therefore being conducted to explore the brain behavior of stressed individuals after listening to Quranic recitation. As a preliminary study, the biosignal of three participants(subjects) was collected using electroencephalogram (EEG), and following by our experimental procedures which involved:1) filling out the DASS- 21(depression anxiety and stress scales),and 2) based on the DASS- 21 scores, EEG data is collected from the subjects before and after listening to the Quranic recitation, and if the subject is stressed, or if the subject is not stressed, only EEG data in the normal state was collected. Topographical maps of the five power bands of EEG for each subject were then created and visualized using Python, and a comparison of these maps was drawn to derive the research results. The result showed that after listening to Quranic recitations, the high Beta power than Alpha that was induced by stress was reduced to be high Alpha power than Beta power, and this indicates the normal state of the subject's brain activities without stress.